A Comprehensive Review on HIV-Associated Dermatologic Manifestations: From Epidemiology to Clinical Management - Mohseni Afshar, Zeinab; Goodarzi, Azadeh; Emadi, Seyed Naser; Miladi, Ronak; Shakoei, Safoura; Janbakhsh, Alireza; Aryanian, Zeinab; Hatami, Parvaneh (International Journal of Microbiology, 2023)
Dermatological disorders are among the most prevalent manifestations of HIV infection/acquired immunodeficiency syndrome (AIDS). In this review, we aimed to characterize the various dermatologic presentations among HIV-infected patients with a detailed categorization of the mucocutaneous signs and symptoms, their etiopathogenic factors, and clinical management. In fact, cutaneous manifestations of HIV are quite various, ranging from AIDS-specific skin eruptions (xerosis, pruritic papular eruptions, eosinophilic folliculitis, and acne), opportunistic infections (herpes simplex, molluscum contagiosum, cutaneous leishmaniasis, bacillary angiomatosis, disseminated histoplasmosis, disseminated cryptococcosis, and zoster) to AIDS-related malignancies (Kaposi’s sarcoma, lymphoma, and nonmelanoma skin cancers) and antiretroviral therapy (ART)-associated drug eruptions. We tried to classify HIV-related cutaneous presentations which can help clinicians for a better understanding of the various specific and nonspecific features of AIDS-associated cutaneous manifestations and management of the condition.